Happy Marriage, Happy Life? Marital Quality and Subjective Well-being in Later Life - Carr, Deborah; Freedman, Vicki A.; Cornman, Jennifer C.; Schwarz, Norbert (Journal of marriage and family, 2014)
The authors examined associations between marital quality and both general life satisfaction and experienced (momentary) well-being among older husbands and wives, the relative importance of own versus spouse's marital appraisals for well-being, and the extent to which the association between own marital appraisals and well-being is moderated by spouse's appraisals. Data are from the 2009 Disability and Use of Time daily diary supplement to the Panel Study of Income Dynamics (N = 722). One's own marital satisfaction is a sizable and significant correlate of life satisfaction and momentary happiness; associations do not differ significantly by gender. The authors did not find a significant association between spouse's marital appraisals and own well-being. However, the association between husband's marital quality and life satisfaction is buoyed when his wife also reports a happy marriage, yet flattened when his wife reports low marital quality. Implications for understanding marital dynamics and well-being in later life are discussed.